Worming steers grazing summer bluestem pasture - E.F. Smith; J.S. Woolfolk (Kansas Agricultural Experiment Station Research Reports, 1973)
One hundred and sixty- three black steers averaging 402 pounds were grazed from May 2 to October 3, 1972, on native bluestem pasture. They were assembled by a buying firm in Memphis, Tenn., and delivered March, 1972, averaging about 350 pounds. They were fed corn silage, alfalfa hay, and about 5 pounds of grain each daily until started on test May 2. They were allotted to different pastures described in Table 1. Even numbered steers in each pasture (about half) received one bolus of thiabendazole (15 grams) as a worming agent. The worming agent did not significant affect gains.
Keywords: Cattlemen' s Day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station); 568; Beef; Steers; Bluestem pasture; Worming